Archives and Historical Accountability: Toward a Moral Theology of Archives - O'Toole, James (Archivaria, 2004)
This essay explores the idea that there is such a thing as "archival theology." After drawing a parallel between the academic discipline of theology on the one hand and archival theory and practice on the other, it focuses special attention on archival moral theology, that branch of the subject which examines moral and ethical behaviour. While professional codes of ethics are useful and necessary, the essay argues that a broader moral vision is necessary. In particular, it adds to familiar discussions of the use of archival records for accountability, a consideration of a long-term, historical accountability for human actions. RÉSUMÉ Cet article explore l'idée qu'il existerait une "théologie archivistique." Après avoir tracé un parallèle entre la discipline universitaire de la théologie d'un côté et la théorie et la pratique archivistique de l'autre, l'auteur porte une attention particulière à la théologie morale des archives, cette section qui examine le comportement moral et éthique. Bien que les codes d'éthique professionnels soient utiles et nécessaires, cet article allègue qu'une vision morale plus large est nécessaire. Il ajoute notamment aux discussions sur l'utilisation des documents d'archives aux fins d'imputabilité, la question de l'imputabilité historique et à long terme des actions humaines.